Wacana Islam Nusantara dan Islam Hadhari dalam Politik Luar Negeri Indonesia dan Malaysia - Hadza Min Fadhli Robby (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2021)
This research investigates the discourse of Islam Nusantara and Islam Hadhari that were developed in the foreign policies of Indonesia and Malayasia, respectively. These two discourses have certain similarities, such as the focus of both discourses to mainstream the issue of moderation and progressivism in Islamic religious life based upon the interpretation of the local wisdom. It is important to highlight that both of these discourses were coming into being through two different contexts. Islam Nusantara was constructed at the era when Muslim world were facing the residues from the failures of Arab Springs: the rise of ISIS as transnational terrorist movement, the rise of Islamophobia politics, and the heightened conflict between Sunni and Shiite. Islam Hadhari came into being at a very different context, where initially Islam Hadhari was proposed as a solution to face the challenge in democratizing Malaysian society amid the rising radicalism and terrorism in global political arena. This research would like to investigate both discourses using international political theology approach as developed by Vendulka Kubálková (2000), which focuses on analyzing the dialectics between religious texts and international political contexts. This research would also use the concept of macroscopical map of relations between religion and foreign policy that were developed by Warner & Walker (2011) to know how islam Nusantara and Islam Hadhari would be eventually adopted as part of Indonesian and Malaysian foreign policy discourses.